Comparison of BlockBuster® Laryngeal Mask Airway, King Vision® Video Laryngoscope, and flexible intubation scope for orotracheal intubation in adult patients with simulated immobilised cervical spine: A randomised controlled trial - Neha Sinha; Kharat Bhat; Samiksha Khanuja; Mahima Gupta; Megha Wadhwani; Pratibha Panjiar (Indian Journal of Anaesthesia)
Background and Aims: Flexible intubation scope, video laryngoscope and supraglottic airway device-guided tracheal intubation are suggested in cervical spine injury patients to avoid further exacerbation of cord injury. This study compared the intubation characteristics of BlockBuster laryngeal mask airway (BBLM), King Vision video laryngoscope (KKVL) and flexible intubation scope (FIS) in patients with simulated immobilised cervical spine. Methods: This study was performed on 120 adult patients with American Society of Anesthesiologists physical status I–II scheduled for elective surgery under general anaesthesia requiring orotracheal intubation. Patients were randomly allocated to Group BBLM, Group KVVL and Group FIS. Time to intubation, first-attempt success rate and complications were recorded and compared between the three groups. Results: There was a significant difference in the mean total time for intubation between the groups (P < 0.0001). The success rate of the first attempt was 75% in Group BBLM, 77% in Group KVVL and 82.5% in Group FIS (P = 0.727). Complications like mucosal damage, oesophageal intubation, and incidence of sore throat and cough were comparable in the three groups. Conclusion: Intubation time was faster with BBLM and KVVL than with FIS in patients with simulated cervical spine immobilisation. The first-attempt success rate and complications were the same for all three devices.